Further Insight into the Photochemical Behavior of Aromatic γ,δ-Epoxy Ketones: A New Approach for Synthesis of 4-Methyleneisochromanols - Li, Bing; Yang, Chao; Xia, Weitao; Xia, Wujiong (Synlett, 2015)
The photochemical behavior of methyl-substituted aromatic γ,δ-epoxy ketones was investigated by irradiation with a 500 W high-pressure mercury lamp in benzene which led to the formation of 4-methyleneisochromanols through δ-hydrogen abstraction–epoxy rearrangement–1,5-biradical cyclization reactions.
Keywords: γ,δ-epoxy ketones; photochemical behavior; 4-methyleneisochromanol; epoxy rearrangement; 1,5-biradical cyclization